Robots and the Gender Pay Gap in Europe - Cevat Giray Aksoy; Berkay Ozcan; Julia Philipp (Institute of Labor Economics (IZA), 2020)
Could robotization make the gender pay gap worse? We provide the first large-scale evidence on the impact of industrial robots on the gender pay gap using data from 20 European countries. We show that robot adoption increases both male and female earnings but also increases the gender pay gap. Using an instrumental variable strategy, we find that a ten percent increase in robotization leads to a 1.8 percent increase in the gender pay gap. These results are mainly driven by countries with high levels of gender inequality and outsourcing destination countries. We then explore the mechanisms behind this effect and find that our results can be explained by the fact that men at medium- and high-skill occupations disproportionately benefit from robotization (through a productivity effect). We rule out the possibility that our results are driven by mechanical changes in the gender composition of the workforce nor by inflows or outflows from the manufacturing sector.
Keywords: J00; J31; J71; 330; industrial robots; gender pay gap; automation; Europe